Assessment of Efficacy (Time Taken During Stage I and Pain Perception) of Customized Lingual Orthodontic System (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: incognito appliance system; ibraces; invisible; pain perception; VAS